ANALYSIS OF THE APPLICABILITY OF THE NON-PROSECUTION AGREEMENT TO THE PRIVILEGED DRUG TRAFFICKING OFFENSE (Reflection and Critique Law Magazine, 2025)
This research seeks to verify whether the non-prosecution agreement is applicable to the privileged drug trafficking offense, as well as whether it is a sufficient and convenient instrument, in theoretical terms, for the disapproval and prevention of this crime. To this end, it begins with the contextualization of negotiated Criminal Justice, highlighting the main characteristics and institutes of the collaboration microsystem in the national criminal justice system. It then analyzes collaborative methods as alternatives to the classical method of criminal prosecution. An examination of the non-prosecution agreement, the central object of this study, follows, emphasizing its legal nature and key characteristics, clarifying its possible applications in the current criminal procedural system, as well as the way it is implemented. Furthermore, it explores the crime of drug trafficking, presenting its historical origin and evolution in Brazilian law, with a focus on the privileged form, as well as reviewing the position taken by the Supreme Federal Court regarding the nature of the offense under article 33, § 4 of Law No. 11,343/06. The study then turns to academic, institutional, and jurisprudential positions on the possible application or not of the non-prosecution agreement to the privileged drug trafficking offense, aiming to identify them and present the respective reasons. Finally, it concludes that, although in theoretical terms, the application of the non-prosecution agreement to the privileged drug trafficking offense is possible, this institute is neither sufficient nor convenient for the disapproval and prevention of this crime. Keywords: Criminal law; Criminal policy, Negotiated criminal justice; Agreement of non-prosecution; Drug trafficking crime.